2020
DOI: 10.1016/j.joca.2019.09.008
|View full text |Cite
|
Sign up to set email alerts
|

The effects of TNF-alpha inhibition on cartilage: a systematic review of preclinical studies

Abstract: Objective: To report the most up-to-date evidence on the effects of tumour necrosis factor (TNF)-alpha inhibition on cartilage with a focus on its clinical relevance. Design: A systematic review was performed by searching PubMed, Embase and Cochrane Library databases. Inclusion criteria were studies of any level of evidence published in peer-reviewed journals reporting clinical or preclinical results written in English. Relative data were extracted and critically analysed. PRISMA guidelines were applied, and r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
39
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(41 citation statements)
references
References 53 publications
1
39
0
1
Order By: Relevance
“…The present study demonstrated that TNFα contributed to OA pathogenesis via NF-κB mechanisms affecting metabolic imbalance in chondrocytes, leading to structural joint damage (39). Similarly, it was recently demonstrated that patients with OA exhibited a notable response to anti-TNF therapy (40), indicating a pivotal role for TNFα in cartilage catabolism. Thus, TNF inhibitors may be a therapeutic option for patients with OA with severe inflammation or TNFα-driven cartilage destruction.…”
Section: Discussionsupporting
confidence: 65%
“…The present study demonstrated that TNFα contributed to OA pathogenesis via NF-κB mechanisms affecting metabolic imbalance in chondrocytes, leading to structural joint damage (39). Similarly, it was recently demonstrated that patients with OA exhibited a notable response to anti-TNF therapy (40), indicating a pivotal role for TNFα in cartilage catabolism. Thus, TNF inhibitors may be a therapeutic option for patients with OA with severe inflammation or TNFα-driven cartilage destruction.…”
Section: Discussionsupporting
confidence: 65%
“…[3][4][5] A systematic review of preclinical studies suggests that TNF-α inhibition promotes cartilage repair in both in vivo and in vitro OA models. 6 There is also evidence to suggest that IL-6 inhibition 7 or knockout (KO) 8 alleviates knee OA cartilage destruction in mice. TNF-α and IL-6 have been shown to induce chondrocyte apoptosis in OA 7,9 and have become a prominent treatment target for OA.…”
Section: Introductionmentioning
confidence: 99%
“…На фоне длительно сохраняющегося провоспалительного потенциала тканей сустава про-исходит значительное снижение репаративных процессов, что в конечном итоге приводит к дезорганизации внеклеточного матрикса и прогрессирующей дезинтеграции хряща в совокупности с другими дегенеративно-дистрофическими внутрисуставными изменениями [9,11].…”
Section: Introductionunclassified